Synthesis, Characterization, and Liquid Crystalline Properties of Phosphazenes Incorporated (E)-3-(4-alkyloxyphenyl)-1-(4-hydroxyphenyl)prop-2-en-1-one - Norashikin Irdawaty, Abd Rahman; Zainab, Ngaini (Institut Kimia Malaysia, 2011)
A series of new substituted cyclotriphosphazenes were prepared by reaction of hexachlorocyclotriphosphazenes, (NPCl2)3 separately with one and six equivalent of (E)-3-(4-alkyloxyphenyl)-1-(4-hydroxyphenyl)prop-2-en-1-one (2a-c) in the presence of base to afford mono[(E)-3-(4-alkyloxyphenyl)-1-(4-hydroxyphenyl)prop-2-en-1one (3a-c) in 18-27% yields and hexakis[(E)-3-(4-alkyloxyphenyl)-1-(4-hydroxyphenyl)prop-2-en-1one (4a-c) in 71-88% yields, respectively. All the synthesized compounds were characterized via elemental analysis (CHN), FTIR, and 1H, 13C and 31P NMR. Their molecular structures were further ascertained through 1H-1H Correlation Spectroscopy (COSY) and Heteronuclear Multiple Quantum Coherence (HMQC). The texture observation was performed under polarizing optical microscopy (POM) over heating and cooling cycles.